Role of Sodium in Determining Alternate Pathways of Aerobic Citrate Catabolism in Aerobacter aerogenes - O'Brien, R. W. (1969)
In contrast to the absolute Na(+) requirement for anaerobic growth of Aerobacter aerogenes on citrate as sole carbon source, aerobic growth of this microorganism did not require the presence of Na(+). However, Na(+) (optimal concentration, 10 mm) did increase the maximal amount of aerobic growth by 60%, even though it did not change the rate of growth. This increase in growth was specifically affected by Na(+), which could not be replaced by K(+), NH(4)(+), Li(+), Rb(+), or Cs(+). Enzyme profiles were determined in A. aerogenes cells grown aerobically on citrate in media of varying cationic composition. Cells grown in Na(+)-free medium possessed all the enzymes of the citric acid cycle including α-ketoglutarate dehydrogenase, which is repressed by anaerobic conditions of growth. The enzymes of the anaerobic citrate fermentation pathway, citritase and oxalacetate decarboxylase, were also present in these cells, but this pathway of citrate catabolism was effectively blocked by the absence of Na(+), which is essential for the activation of the oxalacetate decarboxylase step. Thus, in Na(+)-free medium, aerobic citrate catabolism proceeded solely via the citric acid cycle. Addition of 10 mm Na(+) to the aerobic citrate medium resulted in the activation of oxalacetate decarboxylase and the repression of α-ketoglutarate dehydrogenase, thereby diverting citrate catabolism from the (aerobic) citric acid cycle mechanism to the fermentation mechanism characteristic of anaerobic growth. The further addition of 2% potassium acetate to the medium caused repression of citritase and derepression of α-ketoglutarate dehydrogenase, switching citrate catabolism back into the citric acid cycle.